Detection and Control of Dermatophytosis in Wild European Hedgehogs (Erinaceus europaeus) Admitted to a French Wildlife Rehabilitation Centre - Cécile Le Barzic; Adela Cmokova; Chloé Denaes; Pascal Arné; Vit Hubka; Jacques Guillot; Veronica Risco-Castillo (Journal of Fungi, 2021)
The rising number of European hedgehogs (Erinaceus europaeus) admitted every year to wildlife rehabilitation centres might be a source of concern to animal and public health since transmissible diseases, such as dermatophytosis, can be easily disseminated. This study seeks to evaluate the frequency of dermatophyte detection in hedgehogs admitted to a wildlife rehabilitation centre located near Paris, France, and to assess the risk of contamination in the centre in order to adapt prevention measures. A longitudinal cohort study was performed on 412 hedgehogs hosted at the Wildlife Animal Hospital of the Veterinary College of Alfort from January to December 2016. Animals were sampled once a month for fungal culture. Dermatophyte colonies were obtained from 174 out of 686 skin samples (25.4%). Besides Trichophyton erinacei, Trichophyton mentagrophytes and Nannizzia gypsea were also found. Dermatophyte detection seemed to be associated with the presence of skin lesions, while more than one-third of T. erinacei-positive animals were asymptomatic carriers. Healing required several months of treatment with topical and systemic azoles, but dermatophytosis did not seem to reduce the probability of release. Daily disinfection procedures and early detection and treatment of infected and asymptomatic carriers succeeded in limiting dermatophyte transmission between hedgehogs and humans.